EVALUATION OF THE EFFECT OF A TWIN BLOCK AND A MODIFIED FUNCTIONAL DEVICE ON UPPER AIRWAY VOLUME AND PULMONARY FUNCTION IN PATIENTS WITH A DISTAL OCCLUSION - Drohomyretska, M.S.; Sadeq, A.S.M.; Dienha, O.V.; Pyndus, T.O.; Vyshnevska, H.O.; Shnaider, S.A.; Dorosh, I.V. (World of Medicine and Biology, 2023)
The study was devoted to the comparison of the effectiveness of orthodontic treatment of skeletal forms of distal occlusion using a modified functional appliance and a twin block in terms of the impact on changes in the size of the upper airways and pulmonary function in patients with retrograde mandibular position and upper airway narrowing. The anthropometric and spirometric parameters in the dynamics of orthodontic treatment of 104 children aged 7 to 13 years with skeletal forms of distal occlusion and upper respiratory tract pathology in the period of malocclusion, at the peak of growth (CS3 and CS4 – pubertal stages) were analyzed. The use of functional equipment is a necessary component of orthodontic treatment of children with skeletal forms of distal occlusion, as it allows to correct bite pathology and improve the functioning of the dentition.